A PROGRAM OF PHYSICAL EXERCISES AND TOTAL MOOD DISTURBANCE OF INDIVIDUALS REGISTERED AT ESF / SPRING (Fiep Bulletin - online, 2012)
Quasi-experimental research in order to investigate the influence of an exercise program in the emotional state related to the total mood disturbance of its practitioners. The population was composed of subjects enrolled in the FHS / Spring Cruz Alta / RS. The criteria for inclusion / exclusion of subjects in the sample for spontaneity after signing the term sheet had been signed. It was composed of 14 females with a mean age of 54.64 ± 8.2 years. Evaluation was performed in a class-oriented exercise (30 minutes of aerobic exercise, exercise located 20min 10min and stretching), with application of the instrument before and after exercise. For the assessment of mood states POMS test was used (Profile Of Mood States), which assesses 06 states (Voltage - TS; Depression - SD; Anger - RV; force - VG; Fatigue - FD; Mental Confusion - CM). This test was translated by Brandão et al (1996). We adopted the method of Cross and Mota (1997), to obtain the Total Mood Disturbance (PTH). The data were processed using descriptive statistics, mean and standard deviation and "t" student in SPSS. The study was approved by the Ethics Committee in Research of UNICRUZ 0007.0.417.000-11 under the CAAE. The study concluded that the exercise program has a highly significant influence on the improvement in PTH - Total Mood Disturbance. Physical exercise produces improvements in energy and physical strength, it means that the positive factor of the mood, physical strength in the case when increased has the ability to reduce the negative factors of the mood, tension, depression, anger; Fatigue and confusion, greatly improving the overall mood.
Keywords: Physical Activity; Emotional State; Health.